PENGEMBANGAN KOMIK BERBASIS PETA KONSEP SEBAGAI MEDIA PEMBELAJARAN PADA MATERI SISTEM SARAF DI SMA - Evriyani, Dian; Rusdi, R; Indraswary, Ayu (Biosfer: Jurnal Pendidikan Biologi, 2016)
Comics are one of media which can be used for learning purposes. Attractive visual element of comic allowing students to learn about challenging biology concepts. Therefore, this research was aimed to develop concept map based comic as learning media on Nervous System. This study was conducted from April to June 2016 at SMAN 91 Jakarta, using research and development method. There were six steps had been done continuously: need assessment, objective formulation, material development, instruments development, media development, and try-out and revision. The developed product received very good interpretation in all feasibility try-outs. The average of percentage score for feasibility try-out gained from media experts, material experts, small group of students try-out, and for Biology teacher try-out were 86,5%, 92,6%, 85,4%, 85,7%, and 85,5% respectively. The product’s average percentage of feasibility score was 87,1%, which indicated that the product obtained a very good interpretation. As a conclusion, this concept map based comic was qualified as a learning media on Nervous System in senior high school.